A avaliação de língua inglesa no ENEM : efeitos de seu impacto social no contexto escolar - Blanco, Juliana (Universidade Federal de São Carlos, 2013)
During all life we test and are tested, in many contexts and situations and with many purposes. (MCNAMARA, 2000) One of the most famous tests is the educational one, which can be internal, prepared and applied by the teacher of the subject, or can be external, designed by an expert and applied to students. About external tests, nowadays, in Brazil we have Exame Nacional do Ensino Médio (ENEM). This exam was first applied in 1998 with performance function, to evaluate students at the end of basic education. In 2010, ENEM was changed and one of the changes was the insertion of English language test. The English test part is composed of five multiple choice questions of text comprehension. At this moment, ENEM became a high stake exam in Brazilian context due to its multiple functions: entrance exam, or part of it, in federal universities; way of selection for private universities; and it also continued to be a performance test. As a consequence, the number of people applying the exam grew, and in 2012 it was taken by more than five millions of people. Thus, according to Scaramucci (2010), this exam tends to have consequences in English teaching and learning and in people‟s lives. Therefore, our focus in this study is on the insertion of the English test in ENEM and its implications, which can be positive or negative about English and its subject. It is important to consider the importance of knowing the English language nowadays, because of its hegemony in the world, due to political and social importance of countries where it is spoken. (RAJAGOPALAN, 2010) By this way, this dissertation has the objective of presenting a master research whose focus is discovering and analyzing the social initial impact caused by the insertion of English in the exam, by data collected among students and teachers, all of them involved with studying or preparing students for the exam. This study is qualitative, without testing ready hypothesis, but intending to find out what students and teachers think about ENEM and, mainly, about the English language. The participants of this research project are students and teachers of the last year of high school and from a preparatory course for entrance exam. All of them took ENEM in 2011. Data was collected using questionnaires and interviews with students and teachers of one school and one preparatory course in a city of São Paulo state. An initial impact could be evidenced from data analysis, showing the exam relevance to society and to Language education at regular schools. However, even though the English test in ENEM has been recently applied to students, some consequences are notable and considerable. The analysis showed both external and internal classroom consequences and the opinion of people involved with the exam about ENEM English questions mainly. We believe that the impact will be more evident in some years when the exam is effectively established and teachers are familiar with its format and its construct
Keywords: Linguística; Exame Nacional do Ensino Médio (ENEM); Língua inglesa; Avaliação; Impacto social; ENEM; English language; Test; Impact; LINGUISTICA, LETRAS E ARTES::LINGUISTICA